Digital Transformation and Business Resilience in Crisis Contexts - Dina Noval Madurani; Harold Jay L Cunanan; Nazva Abiya; Fikri Hizryan (CV. Era Digital Nusantara, 2026)
This paper aims to review the role of digital transformation in strengthening business resilience in crisis contexts. The study focuses on the relationship between digital transformation strategy and the multidimensional nature of business resilience. This study uses a conceptual literature review approach. The review synthesizes prior studies on digital transformation, business resilience, organizational resilience, and strategic management. The analysis focuses on how digital technologies are translated into organizational capabilities. The review shows that digital transformation supports business resilience through recovery, adaptation, and anticipation. Digital transformation supports recovery by helping firms maintain operational continuity during disruption. It supports adaptation by enabling firms to redesign business processes and value creation. It also supports anticipation by strengthening information processing and strategic response capabilities. Digital transformation should not be understood merely as technology adoption. It should be viewed as a strategic capability that enables firms to maintain continuity, renew business models, and prepare for future uncertainty. This paper contributes to strategic management literature by integrating digital transformation strategy with the multidimensional concept of business resilience.